ALGAFISNA YES MENINGKATKAN KEAKTIFAN, KREATIVITAS DAN PEMAHAMAN KONSEP FISIKA SISWA KELAS X SMK N 1 KEDUNGWUNI - Nur Fatwa (JURNAL EDUSCIENCE (JES), 2022)
Abstract Abstract physics learning AGAFISNA YES without the help of teaching aids makes students less active and creative so that it has an impact on the low understanding of physics concepts. The lack of teaching aids is an obstacle, to meet the shortage of teaching aids. The teacher applies physics learning by using simple physics teaching aids made by students in groups. ALGAFISNA YES (YouTube Simple Physics Teaching Aid, Education and Socialization) as the right solution to increase activity, creativity and understanding of physics concepts for class X students of SMK N 1 Kedungwuni. Learning physics using ALGAFISNA YES has been implemented since the 2018/2019 school year until the 2020/2021 school year. Through ALGAFISNA YES, it is proven that there is an increase in the average percentage of student activity to 86.90%, student creativity has increased by 22 students' works, and the average understanding of concepts has increased to 80.24. received a positive response on the ALGAFISNA YES Youtube channel and became an inspiration for teachers in other schools. With ALGAFISNA YES, the teacher also won first place in the best practice competition with the theme of online learning at home.Keywords:  ALGAFISNA YES, Student activity, Student creativity, Understanding of physics conceptsAbstrak Pembelajaran fisika yang bersifat abstrak tanpa bantuan alat peraga membuat siswa kuramg aktif dan kreatif sehingga berdamapak terhadap rendahnya pemahaman konsep fisika. Minimnya alat pearaga menjadi kendala, untuk memenuhi kekurangan alat peraga.guru menerapkan pembelajaran fisika menggunakan alat peraga fisika sederhana yang dibuat oleh siswa secara kelompok. ALGAFISNA YES (Alat Peraga Fisika Sederhana Youtube, Edukasi dan Sosialisasi) sebagai solusi yang tepat untuk meningkatkan keaktifan, kreativitas dan pemahaman konsep fisika siswa kelas X SMK N 1 Kedungwuni. Pembelajaran fisika menggunakan ALGAFISNA YES sudah dilaksanakan sejak tahun pelajaran 2018/2019 hingga tahun pelajaran 2020/2021. Melalui ALGAFISNA YES terbukti terjadi peningkatan rerata persentase keaktifan siswa menjadi 86,90%, kreativitas siswa mengalami peningkatan 22 karya siswa, dan peningkatan rerata pemahaman konsep menjadi 80,24. AGAFISNA YES mendapatkan tanggapan positif di chanel Youtube ALGAFISNA YES dan menjadi inspirasi bagi guru di sekolah lain. Dengan ALGAFISNA ini pula guru meraih juara I lomba best practie dengan tema KBM di rumah secara daring. Kata kunci : ALGAFISNA YES, keaktifan siswa, kreativitas siswa, pemahaman konsep fisika